Is Intercropping an Environmentally-Wise Alternative to Established Oil Palm Monoculture in Tropical Peatlands? - Dhandapani, Selvakumar; Girkin, Nicholas T.; Evers, Stephanie; Ritz, Karl; Sjögersten, Sofie (Frontiers in Forests and Global Change, 2020)
Tropical peatlands in Southeast Asia are important ecosystems that play a crucial role in global biogeochemical cycles, with a potential for strong climate feedback loops. The degradation of tropical peatlands due to the expansion of oil palm plantations and their impact on biodiversity and the carbon balance is a global concern. The majority of conversion of Southeast Asian peatlands to agriculture has been by smallholder oil palm farmers, who follow more varied cropping systems compared to industrial plantations, and have better scope for expansion of other alternative varied cropping systems if supported and encouraged. Using previously-published data on peat physicochemical properties, microbial phenotypic community structure and greenhouse gas emissions from small-holder oil palm plantations, we determined that prolonged oil palm monocropping for two generations would result in loss of carbon and peat functional properties that may lead to potential declassification of peatlands. We propose intercropping during the early stages of oil palm as a wise alternative for already-existing plantations in tropical peatlands to ameliorate some of the negative environmental impacts of oil palm on the physio-chemical properties of peat. However, we emphasise the need to more fully explore the sustainability of intercropping systems throughout the life cycle of palm plantations on peatlands, and integrate with current management practices. We also emphasise the further need for research to fully assess the impacts of oil palm intercropping compared to widely-practiced oil palm monocropping. Finally, we suggest changes in government certification policies to encourage intercropping practices by smallholders.